Intervention with institutional caregivers for the purpose of supportive education for disadvantaged children: 3C - Dere, Zeynep; Akagündüz Eğrikılınç, Duygu (Frontiers in Psychology, 2024)
Children in institutional care may have limited access to educational opportunities compared to children in parental care. Improving and enriching the educational practices of these children is important for their well-being. In this study, the Child Development, Communication and Care (3C) Training Program was prepared by the researchers. The 3C education approach emphasizes early childhood development and education. Particular focus is on the use of communication techniques in the education of young children. Our goal with 3C is to increase caregivers' knowledge of child development and support them to communicate effectively with children. Through this curriculum framework, children are encouraged to interact effectively and empathically with others. Therefore, the curriculum framework emphasizes understanding emotions and building trusting relationships as key components in the holistic development of young disadvantaged children. A quasi-experimental design with pre-test-post-control group was used in the study. 16 sessions of 3C were applied to the personnel in the experimental group via distance education. Data were collected from the participants before and after the start of the training program by using the Child Education Competence Scale-Parent Form, Personal Information Form, and Training Evaluation Questionnaire. As a result, significant differences were obtained between the experimental and control groups in favour of the group receiving training (z=3.57, p˂0.05). Accordingly, it can be said that 3C contributes to the holistic development of the child. It is hoped that such work could enhance the developmental outcomes of young children in institutional care and improve the quality of early childhood education.